Analysis of the EU’s Dual VET Promotion Strategy and Its Impact on Spanish VET Stakeholders - Martínez-Izquierdo, Luis; Rommel, Irina (Universidad de Jaén, 2025)
En las últimas décadas la Unión Europea se ha erigido como promotora de la Formación Profesional (FP) dual en los Estados Miembros. La presente investigación analiza y sistematiza las acciones de difusión desplegadas por esta organización internacional. Asimismo, analiza la incidencia de las mismas en los actores de la gobernanza de la FP en España. Para ello, se analiza un total de 35 referencias en materia de FP generadas por esta institución internacional y un conjunto de 13 entrevistas semiestructuradas a representantes del colectivo empresarial, sindical, gubernamental y educativo implicados en la gobernanza de la FP. Los hallazgos concluyen que las distintas instituciones de la Unión Europea han desplegado su actividad en torno a cuatro focos: recomendaciones, aprendizaje por pares, financiación y la Alianza Europea para la Formación de Aprendices. De estos, los dos mecanismos con mayor impacto en los actores españoles han sido las recomendaciones y la financiación condicionada.

In recent decades, the European Union has positioned Dual Vocational Education and Training (VET) as a benchmark for modernisation across Member States. This study systematically analyses the dissemination actions undertaken by this international organisation and their impact on VET governance actors in Spain, specifically at the central level, in Andalusia, and in the Basque Country. To achieve this, the research examines a total of 35 EU-generated VET references including recommendations, conclusions, and declarations; and draws on 13 semi-structured interviews with representatives from the business, trade union, government, and educational sectors involved in VET governance. The findings reveal that various EU institutions have focused their efforts on four main areas: non-binding policy documents, peer learning, funding, and the European Alliance for Apprenticeships. Among these, the most impactful mechanisms for Spanish actors have been the issuance of recommendations and the use of conditional funding.
Análisis de la estrategia europea de difusión de la FP Dual y su impacto en España
Keywords: Formación profesional - Comunidad Europea; Vocational education and training; international organisations; European convergence; Formación profesional; FP Dual; International organisations; Apprenticeships; Policy transfer; Organizaciones internacionales; Transferencia de políticas; Convergencia europea